The influence of social media on mediating gender identity and psychosocial values in the student population of Kazakhstan - Tusupbekova Serikovna Bakhyt; Aliya Saktaganovna Mambetalina; Nuradinov Almat Sabitovich; Kehinde Clement Lawrence; Snezhana Evlogieva Ilieva (Cogent Social Sciences)
With the increasing influence of social media on identity formation, especially among youth, understanding its impact on psychosocial development is essential. This study investigated how social media mediates gender identity and psychosocial values among 437 youths (mean age = 21.9), comprising 27.1% males, 69.4% females, 2.9% non-binary/others, and 0.6% undisclosed. Participants completed a Likert-scale questionnaire, and data were analyzed using IBM SPSS 22 and AMOS 26.0. Structural equation modeling supported the study’s hypotheses, with four fit indices rated as good and one as fair. Although some indices (chi-square, significance probability, RMSEA) did not meet ideal benchmarks, the overall model fit was acceptable. All psychosocial variables; peer influence, self-esteem, social anxiety, and social support; were positively and significantly associated with gender identity. Peer influence emerged as the strongest predictor, followed by social media use, self-esteem, and social support. Social media also showed a significant moderating effect, enhancing the influence of these psychosocial variables on gender identity. These findings suggest that social media plays a powerful role in shaping gender identity, either amplifying or moderating other influences. The study calls for attention from educators, mental health professionals, and policymakers, and recommends further research using longitudinal and culturally diverse data.